Инновационные технологии в логопедической работе - Tyrnova E. A. (Scientific studies and modern education, 2017)
The article is devoted to the use of innovative technologies in the teacher-speech therapist preschool educational institutions. It says that in logopedic work it is possible to combine both pedagogical and psychological and even medical technology. More detail in the article tells of two innovative technologies, namely the didactic cinquaine and mnemonics.
Keywords: инновации; дошкольное образовательное учреждение; логопедия; учитель-логопед; работа; мнемотехника; учреждения; technologies; mnemonics; institutions; preschool; psychological; innovative; teacher-speech; logopedic; pedagogical; educational